1991
DOI: 10.1148/radiology.178.2.1846240
|View full text |Cite
|
Sign up to set email alerts
|

Benign and malignant nodules in cirrhotic livers: distinction based on blood supply.

Abstract: The blood supplies of nodular lesions associated with liver cirrhosis were analyzed in vivo with various imaging modalities. The portal blood supply was evaluated with computed tomography (CT) during arterial portography (CTAP); the arterial blood supply was evaluated with hepatic angiography, CT angiography, CT following intraarterial injection of iodized oil, or ultrasound following intraarterial injection of carbon dioxide microbubbles. A total of 84 surgically confirmed hepatocellular carcinomas (HCCs) (le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
286
3
5

Year Published

1995
1995
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 536 publications
(308 citation statements)
references
References 0 publications
12
286
3
5
Order By: Relevance
“…It has been, therefore, accepted that an abnormal vascular growth could be of diagnostic help to recognize those hepatocellular lesions characterized by an increased risk of neoplastic transformation. 7,10,19 The need for a biological support to the currently available morphological classification is underlined by the recent demonstration that a number of entirely benignlooking LGDNs are monoclonal growths as are a proportion of HGDNs and even HCC. 21 From the present study, we documented that liver nodules, which are considered distinct entities from a morphoclassificative point of view, are characterized by a similar vascular profile.…”
Section: Discussionmentioning
confidence: 99%
“…It has been, therefore, accepted that an abnormal vascular growth could be of diagnostic help to recognize those hepatocellular lesions characterized by an increased risk of neoplastic transformation. 7,10,19 The need for a biological support to the currently available morphological classification is underlined by the recent demonstration that a number of entirely benignlooking LGDNs are monoclonal growths as are a proportion of HGDNs and even HCC. 21 From the present study, we documented that liver nodules, which are considered distinct entities from a morphoclassificative point of view, are characterized by a similar vascular profile.…”
Section: Discussionmentioning
confidence: 99%
“…Underestimation of HCC extension results in early recurrence, and imaging procedures to detect tiny HCC lesions prior to treatment are important. Several studies have reported that CTAP is considered to be the most sensitive technique for the detection of hepatic tumors [13,14], however, this technique is costly, invasive and has a high false-positive rate [15,16]. There are several studies indicating that the combined use of CTAP and CTHA for patients with cirrhosis would be helpful in accurate diagnosis of small nodules [19][20][21][22], and is beneficial in the preoperative evaluation of patients with HCC [23].…”
Section: Discussionmentioning
confidence: 99%
“…Among these imaging techniques, CTAP is one of the most sensitive techniques available for detecting hemodynamic change [13,14], while its distinct disadvantages include invasiveness, high cost and a high rate of false-positive results [15,16]. We have frequently observed that some of the hepatic lesions identified by CTAP and/or CTHA in HCC patients are too small to be diagnosed as additional HCC lesions.…”
Section: Introductionmentioning
confidence: 99%
“…31, No. 4,2000 through an antecubital vein. A helical scanning CT was performed with a section thickness of 7 to 10 mm and a table feed speed of 7 to 10 mm/sec.…”
Section: Imaging For Hepatocellular Nodulesmentioning
confidence: 99%